2014
DOI: 10.1088/1367-2630/16/10/105021
|View full text |Cite
|
Sign up to set email alerts
|

Focus on quantum efficiency

Abstract: Technologies which convert light into energy, and vice versa, rely on complex, microscopic transport processes in the condensed phase, which obey the laws of quantum mechanics, but hitherto lack systematic analysis and modeling. Given our much improved understanding of multicomponent, disordered, highly structured, open quantum systems, this 'focus on' collection collects cuttingedge research on theoretical and experimental aspects of quantum transport in truly complex systems as defined, e.g., by the macromol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Coherence in various aspects of exciton and charge carrier dynamics, its meaning, and its importance for processes relevant for optoelectronic devices have been debated, and it is a topic of considerable interest. ,,,, In the context of energy transfer, examples of coherent effects include a so-called “super-transfer”, which is the exceptional enhancement of the energy transfer rate (in spite of the incoherent nature of the transfer) and a wave-like (rather than hopping-like) excitation transfer between the donor and acceptor which simultaneously realizes different energy transfer pathways, altering energy transport properties through quantum interference . In the context of other important aspects of exciton physics, Chan et al and Bakulin et al showed (using TR-2PPE and 2DES, respectively) how coherent coupling enables efficient singlet fission in Tc and functionalized Pn films (Section ).…”
Section: Exciton Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coherence in various aspects of exciton and charge carrier dynamics, its meaning, and its importance for processes relevant for optoelectronic devices have been debated, and it is a topic of considerable interest. ,,,, In the context of energy transfer, examples of coherent effects include a so-called “super-transfer”, which is the exceptional enhancement of the energy transfer rate (in spite of the incoherent nature of the transfer) and a wave-like (rather than hopping-like) excitation transfer between the donor and acceptor which simultaneously realizes different energy transfer pathways, altering energy transport properties through quantum interference . In the context of other important aspects of exciton physics, Chan et al and Bakulin et al showed (using TR-2PPE and 2DES, respectively) how coherent coupling enables efficient singlet fission in Tc and functionalized Pn films (Section ).…”
Section: Exciton Physicsmentioning
confidence: 99%
“…Exciton transport in organic semiconductors is important for many optoelectronic applications, including OPVs and OLEDs. Exciton quantum transport was studied theoretically; for example, several studies in light-harvesting systems and in 1D molecular assemblies focused on the effects of traps and dynamic disorder on the coherent transport. Pelzer et al modeled the efficiency of exciton quantum transport in light-harvesting systems and demonstrated that, in the presence of a trap, quantum transport is most sensitive to changes in spatial correlation in the region near the trap.…”
Section: Exciton Physicsmentioning
confidence: 99%
“…Inspired by the recent achievements in quantum biology [14][15][16][17][18][19], Vaziri and Plenio proposed a quantum model for the KcsA selectivity filter [1]. They compare ion-channel dimensions with the ion thermal wavelength to conjecture that the underlying dynamics for transport and selectivity might not be entirely classical.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much excitement in recent years about the observation of surprisingly long-lived quantum coherence (the presence of nonzero off-diagonal elements in a quantum mechanical density matrix) in the excitation energy transfer in photosynthetic systems. Since being first observed, it has been suggested that this coherence may be important for efficient transfer of the electronic excitation. ,,,, …”
Section: Introductionmentioning
confidence: 99%